The Impact of Water Sporting Events on Attitudes Toward Physical Activity: Motivational Profiles of Participants in Modern and Traditional Water Events - Młodzik, Maciej; Kazimierczak, Marek; León-Guereño, Patxi; Tapia-Serrano, Miguel Angel; Malchrowicz-Mośko, Ewa (Frontiers in Psychology, 2021)
The aim of this paper is to analyze the relationship between attitudes towards physical activity and participation in water sports events and to recognize main motives of involvement in this kind of events. A written paper–pencil diagnostic survey was conducted among 394 participants of two traditional and two modern sports events on the water held in Poland to check if innovative events are needed in society– if they cause an increase in interest in physical activity. The results showed that modern sports events on the water do not have more power to attract physically inactive people than traditional water events, do not cause a greater desire to lead an active lifestyle and do not encourage people more to regularly practice water sports. Modern events, compared to traditional events, are only a one-time experience and the surveyed people more often want to return to traditional sports events which provided participants with positive emotions at a higher level than a modern event. In the case of socio-demographical variables, there is no statistically significant relationship between gender and choice of modern or traditional event but older people are more likely to choose a traditional event than younger people; modern water events are an attractive offer primarily for young people under 30 years of age. Modern events more often attract people with higher education. However, it turned out that a modern event on the water more often attracts people who have not had any experience with this sport discipline than people who chose traditional water events. Moreovoer,, modern events are therefore effective in promoting water sports in Polish society. It was distinguished five main groups: healthy lifestyles managers, lovers of sports emotions, water sports malcontents, water sports enthusiasts and neutrals to water sports. We checked what are the gender-related motives of participation in modern and traditional water events: social and health-related motives resulted more important for women and men participating in modern water events. The research results showed that the impact of sporting events on the promotion of physical activity and present the motivations for participation in modern and traditional water sporting events.